Antecedentes da adoção do hábito alimentar saudável a partir do modelo de crenças em saúde estendido e dos estágios da mudança - Paola Matos Almeida (2019)
Social marketing is na intervention strategy that seeks to influence changes in behavior directed towards health and well-being. One of the health topics that have come to the fore is noncommunicable diseases (NCDs), wich are associated with a number of risk factors, including unhealthy diet, wich is the focus of this work. Adoption of a healthy eating habit would be onde way of encouraging health promotion and reducing risk factors for NCDs. Among the main theories used in this type of study are the health belief model (HBM) and stage of change, wich were chosen as the two main approaches in this research, wich sought to understand the antecedentes of the adoption of the healthy eating habit and the stages of the behaviour change. Therefore, na extended HBM was proposed, with the inclusion of the constrcts health conscious identity and healthy eating knowledge, scale whose was developed and validated. The data collection was performed by the survey method, in a non-probabilistic sample, obtaining a total of 855 responses. Seeking to understand the stages of change, the participants were also classified according to the stage with which they identify themselves. The data analysis was performed by a structural equations modeling and a multi-group analysis were applied. The results pointed to the validation of the scales, including the healthy eating knowledge scale, and also indicated that the proposed model explained 65,10% of the variability for healthy eating habits. In addition, the multi-group analysis identified particularities and similarities between the constructs analyzed and the stages of change, identifying that benefits and barriers are the main antecedentes of healthy eating habits and that the proposed model explained the highest percentage of behavioral variability in preparation stage (65,4%). These results helped to guide more appropriate initiatives from the interventions proposed by social marketing.